Blockage of sphingosine‐1‐phosphate receptor 2 attenuates allergic asthma in mice - Park, Soo‐Jin (Br J Pharmacol, 2019)
BACKGROUND AND PURPOSE: Sphingosine‐1‐phosphate 2 (S1P(2)) receptors have been implicated in degranulation of mast cells. However, functions of S1P(2) receptors have not been investigated in an in vivo model of allergic asthma. EXPERIMENTAL APPROACH: Using an ovalbumin (OVA)‐induced asthma model, the function of S1P(2) receptors was evaluated in S1P(2)‐deficient mice or in mice treated with JTE‐013, a selective S1P(2) antagonist. Bone marrow‐derived dendritic cells (BMDCs) were used to investigate the roles of S1P(2) receptors in dendritic cell maturation and migration. KEY RESULTS: Eosinophil accumulation and elevated Th2 cytokine levels in bronchoalveolar lavage fluid and inflamed lung tissues were strongly inhibited by administration of JTE‐013 before OVA sensitization, before OVA challenge, and before both events. In S1P(2)‐deficient mice, allergic responses were significantly lower than in wild‐type mice. LPS‐ and OVA‐induced maturation of BMDCs was significantly blunted in dendritic cells from S1P(2)‐deficient mice and by treatment with JTE‐013. Migrations of immature and mature BMDCs were also dependent on S1P(2) receptors. It was found that OVA‐challenged mice into which in vitro OVA primed BMDCs from S1P(2)‐deficient mice were adoptively transferred, had less severe asthma responses than OVA‐challenged mice into which OVA‐primed BMDCs from wild‐type mice were adoptively transferred. CONCLUSIONS AND IMPLICATIONS: Pro‐allergic functions of S1P(2) receptors were elucidated in a murine asthma model. S1P(2) receptors were involved not only in maturation and migration of dendritic cells in the sensitization phase but also in mast cell degranulation in the challenge phase. These results suggest S1P(2) receptor as a therapeutic target for allergic asthma.